KRITIK PENYELENGGARAAN SISTEM JAMINAN SOSIAL NASIONAL DI INDONESIA - Nanang Sri Darmadi (UNISSULA, 2017)
In order to create legislation that is consistent with the values of Pancasila. The background of that legislation created no objective and value-free, but the law is born of ideology complete with doctrine and the value in it. Critics of the statute of the national social security system should be done, because justice embodied therein are not final. Law will always be in the process of being in accordance with the development needs of the community.